Social Security Uncertainty and Demand for Retirement Saving. (17th December 2020) - Jappelli, Tullio; Marino, Immacolata; Padula, Mario
Abstract : The life‐cycle model predicts an association between increased demand for retirement saving and the level of expected future social security benefits. The precautionary saving model shows that the risk associated to future benefits also matters. If social security benefits become more uncertain, individuals should react by increasing their demand for retirement saving. To assess the empirical relevance of this mechanism, we relate individual level measures of social security risk to demand for retirement saving vehicles. Using the Bank of Italy Survey of Household Income and Wealth, we find higher participation in private pension funds among individuals who expect lower and more uncertain social security benefits.